2021
DOI: 10.1186/s13287-021-02620-2
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapy for ameliorating intrauterine adhesion and endometrium injury

Abstract: Intrauterine adhesion refers to endometrial repair disorders which are usually caused by uterine injury and may lead to a series of complications such as abnormal menstrual bleeding, recurrent abortion and secondary infertility. At present, therapeutic approaches to intrauterine adhesion are limited due to the lack of effective methods to promote regeneration following severe endometrial injury. Therefore, to develop new methods to prevent endometrial injury and intrauterine adhesion has become an urgent need.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 127 publications
(174 reference statements)
1
37
0
Order By: Relevance
“…IUA is mainly characterized by hypomenorrhea or amenorrhea [ 6 ]. The purpose of IUA treatment is to control relevant symptoms, promote endometrial repair and regeneration, and reduce the incidence of readhesion as well as complications such as recurrent abortion and secondary infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IUA is mainly characterized by hypomenorrhea or amenorrhea [ 6 ]. The purpose of IUA treatment is to control relevant symptoms, promote endometrial repair and regeneration, and reduce the incidence of readhesion as well as complications such as recurrent abortion and secondary infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial trauma caused by surgery, including abdominal and hysteroscopic myomectomy, septectomy, and any other intrauterine surgery, is the leading contribution to the occurrence of IUA [ 4 ]. IUA has become a common gynecological disease and is characterized by a series of clinical manifestations such as oligomenorrhea, dysmenorrhea, amenorrhea, recurrent abortion, and infertility, posing serious damage to women's reproductive function [ 5 , 6 ]. Previous studies have shown that hysteroscopic adhesiolysis was most commonly used for the clinical treatment of IUA, with the placement of antiadhesion biological adhesive products in the intrauterine cavity and location of intrauterine devices for 2 to 3 months, or retention of the sacculus in the intrauterine cavity for 5–7 days and oral therapy of estrogen and progesterone drugs for 3 months after surgery [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, stem cell transplantation for endometrial repair still has long-term safety and efficacy limitations, such as preservation difficulty, tumorigenicity, and low homing rates of transplanted cells. In addition, there is no uniform guidance or consensus available for a clinical reference regarding stem cell-related therapies ( Bai et al, 2019 ; Song et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, stem cells have been found to have self-renewal and multi-directional differentiation potential, with broad prospects for the treatment of tissue damage involving the uterine cavity ( 10 ). Allogeneic stem cells are widely used in experiments because of their convenient extraction and easy access.…”
Section: Introductionmentioning
confidence: 99%